Peran Tata Kelola Ruang Kelas dalam Mendukung Proses Pembelajaran yang Efektif di Sekolah Dasar - Mustikaati, Wina; Pratiwi, Putri Anandika; Fa’izah, Fitri Nur; Anwar, Azizah Diyah; Yusuf, Devianty; Marisa, Dias (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Classroom management is a crucial aspect in creating a conducive environment for the learning process. This study aims to examine the role of classroom management in supporting effective learning in elementary schools. Focusing on physical arrangement, emotional conditions, and classroom organization, this research finds that good classroom management can enhance students’ focus and concentration, support social interaction, and create a comfortable learning atmosphere. Additionally, the use of technology and flexibility in teaching methods are also key factors in maximizing students’ learning experiences. This study suggests the importance of planning and implementing effective classroom management strategies to support optimal learning quality.